Influential factors on oral health status of the elderly Iranians: A Path analysis - Fartash Tolou, Azadeh; Jadidfard, Mohammad Pooyan; Ghasemi, Hadi; Boroumand, Farzaneh; Namdari, Mahshid; Khoshnevisan, Mohammad H. (Journal of Contemporary Medical Sciences, 2022)
Objectives: This study aimed at assessing the influential factors on oral health status of the elderly Iranian population (65 to 74 years of age) by using Path analysis. Methods: This study was conducted on 7,521 elderly individuals participating in the Iranian National Oral Health Survey in 2012. After data collection process, initially decayed, missing, and filled teeth (DMFT) index as well as functional health (FH) index were evaluated in this study by using clinical data. The socio-economic status (SES), insurance type (IT), dental attendance pattern (DAP), reason of attendance (R of A), tooth cleaning (TC), and nutritional pattern (NP) were evaluated according to responses provided to the questions in the questionnaire by participant. Path analysis was applied to analyze the patterns between these variables and DMFT and FH index. Results: The participants’ mean DMFT was 26.6±8.03, and the median FH was 0 (0.10). Path analysis revealed that seniors with higher SES, and having a dental insurance with greater coverage had a direct effect on more regular DAP, and indirect effect on improvement of FH and reduction in DMFT index. More regular DAP had a direct effect on improvement of FH, and reduction of DMFT index. Also, NP with lower risk of caries had a direct effect on improvement of FH and reduction of DMFT index. Conclusion: Out of all the evaluated factors, IT, SES, DAP, and NP demonstrated to be particularly important and significantly affecting DMFT and FH indices in the elderly population. Out of all aforementioned factors, IT in low SES individuals was more important for obtaining required oral healthcare services. Apparently, seniors’ oral health is absolutely in need of special attention with particular focus on providing access to early prevention and care.